Critical Discourse Analysis of Online News Texts: “Pakar Sebut Pemilih Prabowo Cenderung Beralih ke Sandi Ketimbang Anies” - Nur Afnita Asfar; Brama Kumbara Omar; Indah Permata Sari; Nurdin; Riskayani Djamaleng (CV Wahana Publikasi, 2022)
This research is intended to analyze a news text entitled “Pakar Sebut Pemilih Prabowo Cenderung Beralih ke Sandi Ketimbang Anies” based on the Norman Fairclough’s Critical Discourse Analysis. This research aims to examine the construction of news about the Prabowo voters tend to switch to Sandi instead of Anies. The main data was obtained from CNN Indonesia.com. In analysing the data, researchers used Norman Fairclough analysis model that focuses on the three dimensions, namely text dimension, discourse dimension, and socio-cultural dimension. The results shown that the tendency of news texts to be more in favor of Sandiaga Uno, who is predicted to run in the 2024 presidential election. Through the news texts, the contrast of several parties is shown, which favors Sandiaga Uno. Furthermore, researcher assumed that news text is not only as a media for announcement, however news text as a social construction that is full of power that somehow can marginalized someone.